Green Matters: Carbonless Footprint. (Kanopy Streaming, 2016)
As we travel through life, all of us leave footprints behind. At times these prints are wider and deeper than they should ever be. So how does one go about lightening their step and reducing the imprint? Well, by doing what others have chosen to do; share, renew, reuse and rethink new ways of doing old things. What's your idea?